Different forms of triangular neutrosophic numbers, de-neutrosophication techniques, and their applications - Chakraborty, Avishek; Mondal, Sankar Prasad; Hosseini, Seyedali Ahmadian; Senu, Norazak; Alam, Shariful; Salahshour, Soheil (MDPI, 2018)
In this paper, we introduce the concept of neutrosophic number from different viewpoints. We define different types of linear and non-linear generalized triangular neutrosophic numbers which are very important for uncertainty theory. We introduced the de-neutrosophication concept for neutrosophic number for triangular neutrosophic numbers. This concept helps us to convert a neutrosophic number into a crisp number. The concepts are followed by two application, namely in imprecise project evaluation review technique and route selection problem.